More to Tell About Billa! Asimānum/Šimānum and the Early and Middle Bronze Ages at Baˁšīqā, Iraq - Edmonds, Alexander Johannes; Creamer, Petra M. (2023)
Despite being one of the most prominent and best-documented northern client states of the Ur III state, the city of Asimānum/Šimānum remained unlocalized. Here, we demonstrate through both historical-geographical and philological argumentation and archaeological evidence that it must correspond to later Middle and Neo-Assyrian Šibaniba, modern Tell Billa, northern Iraq. Building upon this finding, we propose a new history of Tell Billa during the Early and Middle Bronze Age.